2020
DOI: 10.1111/aej.12437
|View full text |Cite
|
Sign up to set email alerts
|

Optimal antimicrobial concentration of mixed antibiotic pastes in eliminating Enterococcus faecalis from root dentin

Abstract: This study aims to identify the optimal concentrations of triple antibiotic paste (TAP), modified triple antibiotic paste (mTAP) and double antibiotic paste (DAP) that could completely eradicate Enterococcus faecalis in dentinal tubules. One hundred and ninety extracted human premolars inoculated with E. faecalis were medicated with calcium hydroxide and mixed antibiotic pastes (TAP, mTAP and DAP at 0.1, 1.25, 5, 10 and 20 mg mL−1 of each drug) for seven days before being frozen, pulverised and cultured. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As the antibiotic loading increased the mean inhibition zone, however, bacteria can still survive the intracanal drug due to their deep involvement in the dentinal tubules and canal irregularities. 51 Therefore, from a clinical standpoint, the dentin slice model 52 was used to evaluate the effect of injectable hydrogel on A. naeslundii biofilm and visualized using SEM and CLSM (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…As the antibiotic loading increased the mean inhibition zone, however, bacteria can still survive the intracanal drug due to their deep involvement in the dentinal tubules and canal irregularities. 51 Therefore, from a clinical standpoint, the dentin slice model 52 was used to evaluate the effect of injectable hydrogel on A. naeslundii biofilm and visualized using SEM and CLSM (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…11 This finding was supported by Dewi et al reported E. faecalis colonized in dentinal tubules was not affected and remained after being treated with CaOH. 12 Hence, even with the use of medicaments that possess antibacterial properties, it is hard to eradicate E. faecalis from the root canal. E. faecalis also has resistance toward CaOH by the formation of biofilm alongside surviving in alkaline conditions up to a pH of 11.5 for more than 10 days.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sadek et al [ 31 ] demonstrated that DAP was able to completely eliminate Enterococcus faecalis (E. faecalis) biofilm from radicular human dentin specimens. Moreover, Dewi et al [ 32 ] found that TAP, modified TAP (at 5, 10 and 20 mg mL −1 of each drug), and DAP (at 10 and 20 mg mL −1 of each drug) were capable of significantly eliminating E. faecalis , while CH did not show significant efficacy. In regards to biocompatibility, Khoshkhounejad et al [ 33 ] showed DAP and TAP had similar favorable effects at most of the tested concentrations and could be considered safe materials.…”
Section: Introductionmentioning
confidence: 99%